Lanternfish larvae from the Agulhas current (SW Indian Ocean) - M. Pilar Olivar; H. G. Moser; L. E. Beckley (Scientia Marina, 1999)
This paper is presented as a guide to assist in identifying larval stages of lanternfish (family Myctophidae) of the Agulhas Current region. The work is based on the larvae collected during three cruises conducted off the eastern coast of South Africa from 29°S to 34°S in 1990 and 1991. The larval distributions obtained from these surveys are summarised briefly. Generally, only literature citations are given for species of the region whose larvae have been described previously. Descriptions are limited to those species for which complete larval development have not been published previously and to those species not known to spawn in the region, to compare larval features with those from regions where the species is known to spawn (i.e., Benthosema fibulatum, B. pterotum, Hygophum proximum, Lampadena luminosa, Myctophum selenops, Notoscopelus caudispinosus and Triphoturus nigrescens). Also, diagnostic characters and illustrations are presented for species which may be difficult to identify in some developmental stages, particularly the early larval stages (i.e., Benthosema suborbitale, Bolinichthys spp., Ceratoscopelus townsendi, Diogenichthys panurgus, Myctophum phengodes, Lobianchia dofleini, L. gemellarii and Scopelopsis multipunctatus).